NEGATIVE AND POSITIVE EFFECT OF BACKWASH ON TOEIC TEST - Darmaliana -; Eli Yeny (Politeknik Negeri Sriwijaya, 2016)
Test is a systematic procedure for observing person and describing them with either a numerical scale or a category system. A test is given to know the students’ achievement on their learning. There is a test affects on teaching and learning which is called backwash. Backwash could be positive and negative. Negative washback involve the teacher, students and the school’s program. However, if the assessment of the tesr reflects the skill and content taught in the classrom, the positive washback will be occured.